The Timing of Exposure in Clinic-Based Treatment for Childhood Anxiety Disorders. (January 2013) - Gryczkowski, Michelle R.; Tiede, Michael S.; Dammann, Julie E.; Brown Jacobsen, Amy; Hale, Lisa R.; Whiteside, Stephen P. H.
The present study examines treatment length and timing of exposure from two child anxiety disorders clinics. Data regarding symptoms and treatment characteristics for 28 youth were prospectively obtained through self, parent, and therapist report at each session. Information regarding length of treatment, timing of exposure initiation, and drop-out rates were compared with those obtained through efficacy and effectiveness trials of manualized treatment for anxious youth. Findings from the authors' clinical data revealed significantly shorter treatment duration with exposures implemented sooner than in the previous studies. Dropout rates were significantly higher than in the efficacy trial but comparable with the effectiveness trial. Outcome data from a subset of eight patients revealed large effect sizes. These findings suggest that effective treatment can be shorter and more focused on exposure than is often outlined in manuals and have important implications for outcome research and dissemination.